Inhibitory-κB Kinase (IKK) α and Nuclear Factor-κB (NFκB)-Inducing Kinase (NIK) as Anti-Cancer Drug Targets - Andrew Paul; Joanne Edwards; Christopher Pepper; Simon Mackay (Cells, 2018)
The cellular kinases inhibitory-κB kinase (IKK) α and Nuclear Factor-κB (NF-κB)-inducing kinase (NIK) are well recognised as key central regulators and drivers of the non-canonical NF-κB cascade and as such dictate the initiation and development of defined transcriptional responses associated with the liberation of p52-RelB and p52-p52 NF-κB dimer complexes. Whilst these kinases and downstream NF-κB complexes transduce pro-inflammatory and growth stimulating signals that contribute to major cellular processes, they also play a key role in the pathogenesis of a number of inflammatory-based conditions and diverse cancer types, which for the latter may be a result of background mutational status. IKKα and NIK, therefore, represent attractive targets for pharmacological intervention. Here, specifically in the cancer setting, we reflect on the potential pathophysiological role(s) of each of these kinases, their associated downstream signalling outcomes and the stimulatory and mutational mechanisms leading to their increased activation. We also consider the downstream coordination of transcriptional events and phenotypic outcomes illustrative of key cancer ‘Hallmarks’ that are now increasingly perceived to be due to the coordinated recruitment of both NF-κB-dependent as well as NF-κB–independent signalling. Furthermore, as these kinases regulate the transition from hormone-dependent to hormone-independent growth in defined tumour subsets, potential tumour reactivation and major cytokine and chemokine species that may have significant bearing upon tumour-stromal communication and tumour microenvironment it reiterates their potential to be drug targets. Therefore, with the emergence of small molecule kinase inhibitors targeting each of these kinases, we consider medicinal chemistry efforts to date and those evolving that may contribute to the development of viable pharmacological intervention strategies to target a variety of tumour types.